Study on the Hysteresis Effect of the Stability of Longyangxia Dam Bank Slope with the Fluctuation of Water Level. (20th January 2023) - Yuan, Guangxiang; Wang, Hu; Huang, Zhiquan; Zhang, Luqing
Abstract : Reservoir landslide is a common geological disaster during the operation of hydropower projects. The fluctuation of reservoir water level is an important factor that induces slope instability. The natural slope will gradually lose stability under the rapid rise and fall of reservoir water level. A variety of landslide examples show that, on the premise of not suffering from extreme environmental conditions, the reservoir landslide often occurs after the rapid fluctuation of the reservoir water level for a period of time, and there is a certain time difference between its instability failure and the rapid rise and fall of the reservoir water level. In order to study the hysteresis effect between the stability change of the reservoir slope and the fluctuation of the reservoir water level, taking the Chana landslide in the reservoir area of Longyangxia Hydropower Station as an example, combining the field survey, geological survey data, and the actual change of the reservoir water level, the finite element simulation software is used to restore the actual working condition, and the research is carried out from three aspects of slope seepage field, displacement field, and stability. The results show the following: (1) The hysteresis of slope seepage change during the rising period of reservoir water level is more obvious than that during the falling period of reservoir water level. The deformation potential of Chana landslide is greater during the falling period of reservoir water level, while the deformation is restrained during the rising period of reservoir water level. (2) The incremental displacement simulation results of Chana landslide show that there are deformation incubation period and deformation release period of Chana landslide. The deformation incubation period occurs during the rapid rise and fall of reservoir water level, and the deformation release period occurs during the stable change of reservoir water level. (3) The incremental displacement produced during the deformation release period of the slope is large, but the slope remains stable, which reflects the existence of the internal antisliding mechanism of the landslide from the side. (4) The stability coefficient of Chana landslide changes greatly during the drawdown period. When the drawdown rate of water level is kept at 0.03~0.07 m/d, the stability coefficient of Chana landslide changes slightly and the slope is relatively stable.